Efisiensi Kinerja Rantai Pasok Beras Organik “Beras Raos” - Rizqia Fauziah; Endang Tri Astutiningsih; Neneng Kartika Rini (Hasanuddin University, 2021)
Nowadays people are starting to realize the importance of healthy food, such as organic rice. It's just that economically the rice agricultural sector still faces various problems, one of which is the selling price at the farm level which is still relatively low, this is because the supply chain is still long and the supply chain system is less than optimal. The purpose of this study was to analyze the performance efficiency of the organic rice supply chain